The development of a high functional continuous filtration system for sericite powders - Choi, Heekyu; Bayanjargal, Ochirhuyag; Tsubaki, JunIchiro; Mori, Takamasa; Sugimoto, Tadamitsu; Lee, JungEun (Korean Journal of Chemical Engineering, 2008)
A cake-less continuous filtration equipment has been developed based on an evaluation of inorganic powder slurry characteristics by many kinds of measurement methods, such as a sedimentation test under gravity and a hydrostatic pressure test. We have been developing a high-performance cake-less filtration system in which a condensed inorganic powder slurry layer maintains its fluidity. The development of this novel filtration system has allowed us to cease the scraping operation of the cake as well as to collect the highly condensed slurry more easily. These results clearly show that a new device may be realized for the deposition of highly condensed, fluid slurries. It is confirmed that the concentration of the condensed slurry amounted to 35 vol% while still retaining fluidity. The specifications of our new filtration system and its operation conditions for scale-up can be determined by theoretical methods. There is good potential for successfully collecting high condensation slurry more easily in a multiple filter system.